Bioemulsifier production byMicrobacterium SP. strains isolated from mangrove and their application to remove cadmiun and zinc from hazardous industrial residue - Aniszewski, Erick (Sociedade Brasileira de Microbiologia, 2010)
The contamination of ecosystems with heavy metals is an important issue in current world and remediation technologies should be in according to environmental sustainability concept. Bioemulsifier are promising agents to be used in metal removal and could be effective to many applications in environmental industries. The aims of this work was screening the potential production of bioemulsifier by microorganisms isolated from an oil contaminated mangrove, and evaluate cadmium and zinc removal potential of those strains from a hazardous industrial residue. From that, bioemulsifier-producing bacteria were isolated from urban mangrove sediments. Four isolates were identified as Microbacterium sp by 16S rRNA analysis and were able to reduce up to 53.3% of culture medium surface tension (TS) when using glucose as carbon and energy source and 20.2% when sucrose was used. Suspensions containing bioemulsifier produced by Microbacterium sp. strains show to be able to remove cadmium and zinc from contaminated industrial residue, and its ability varied according carbon source. Significant differences in metal removal were observed by all strains depending on the carbon source. When glucose was used, Cd and Zn removal varied from 17 to 41%, and 14 to 68%, respectively. However, when sucrose was used it was observed only 4 to a maximum of 15% of Cd removal, and 4 to 17% of Zn removal. When the same tests were performed after ethanol precipitation, the results were different: the percentages of removal of Zn (7–27%) and Cd (14–32%) were higher from sucrose cultures. This is the first report of heavy metals removal by bioemulsifier from Microbacterium sp.